Financial development and the capital flow allocation puzzle in developing Asia - John Beirne; Pradeep Panthi (Asian Development Bank Institute (ADBI), 2024)
Using a panel regression approach across 13 developing Asian economies from 1996Q1 to 2019Q4, this paper examines the extent of financial development as a transmission channel for mediating the "allocation puzzle" in capital flows. This puzzle pertains to why capital seems to flow to economies with lower rather than higher productivity growth. We find that while portfolio equity and debt investment flows are negatively related to total factor productivity (TFP) in developing Asia, thereby contradicting the predictions of traditional neoclassical growth models, financial development significantly mitigates this effect. This is particularly the case at earlier stages of financial development and convergence towards a frontier. For foreign direct investment, although we find that there is no direct allocation puzzle in developing Asia, financial development can hamper the stimulatory effect of TFP for highly financially developed economies given diminishing marginal returns.
Keywords: F20; F30; F41; 330; international capital flows; total factor productivity; financial development; developing Asia